ANALISIS ZAT PEMANIS BUATAN PADA MINUMAN JAJANAN YANG DIJUAL DI PASAR TRADISIONAL KOTA MANADO - Nurain A. Hadju; Thelma D.J. Tuju; Maya M. Ludong; Tineke M. Langi (COCOS, 2013)
ABSTRACTDrinks snacks is one product with a sweet taste that can be found, one in the traditional market town ofManado. In the manufacturing procces, manufacturers often use artificial sweeteners to replace naturalsweeteners in order to lower production costs. Artificial sweeteners are the most widely used is the cyclamateand saccharin. In some studies it was found that the use of artificial sweeteners that do not qualify will causecarcinogenic diseases. This study aims to analyze the levels of artificial sweeteners as food additives inbeverages snacks sold in the traditional market town of Manado. The study uses survey. The samples used weresnacks beverages like cendol ice, teler ice, coconut ice, and syrup ice sold in six traditional market town ofManado. This location is chosen according to the overall market located in the market town of Manado PerumPaniki, Paal 2, Tuminting, Bersehati, Karombasan, and Bahu. Sampling as many as 16 samples in whichsamples cendol ice, teler ice 4 samples, coconut ice 1 sample, and syrup ice 2 samples. Conducted a qualitativeanalysis of samples for the presence of cyclamate and saccharin in content of the sample followed by aquantitative analysis to measure the level of artificial sweeteners contained in the sample. The results showedthat in 16 samples of drinks snacks that are six traditional market town of Manado, containing no artificialsweeteners saccharin and two samples of syrup containing artificial sweetener cyclamate. Samples containingcyclamate syrup is red syrup and yellow syrup. Cyclamate levels found in red syrup of 931.98 mg / kg andyellow syrup of 848.65 mg / kg. According to the ISO limit of safe consumption of cyclamate in similar syrup is500 mg / kg, so it can be concluded that cyclamate levels have exceeded the allowed threshold value.Keywords: Snacks drinks, artificial sweeteners, cyclamate, syrup ice